Early severe IUGR: purpose of a case and review of the literature - Ayala Yauri, Maryllini (2021)
Intrauterine growth restriction is defined as a fetus that does not reach its growth potential. The early (<32 weeks) and late (> 32 weeks) presentations have differential but not exclusive characteristics; in relation to the degree of placental obstructive compromise that affects the severity of the hemodynamic manifestations. For its diagnosis, follow-up and management, we have a multivessel Doppler evaluation, which provides information on the deterioration and the risk of intrauterine mortality, allowing to establish the opportune moment of birth. We present the report of a case of early-onset intrauterine growth restriction with severe Doppler alteration evaluated by our department and review the pathogenesis, clinical, and diagnostic approach and management of this condition.